Morbidity Profile of OPD Patients of An Urban Health and Training Center: A Tool for The Health Planners - Yadav, Vikas; Manjunath SR; Mukherji, S; Ramakrishnan, TS (National Journal of Community Medicine, 2015)
Objectives: The objective of the study is to determine the morbid- ity profile of patients attending the OPD at urban health and training centre (UHTC) under the Dept. of Community Medicine, AFMC, Pune, as per age, sex and in different season of the year. Method: Data for 12 months from Jul 12 to Jun 13 was collected from the OPD registers of the consultant medical officer. Patients who visited for medicine collection or review were excluded from the study. The patients were grouped into age groups of <5, 5-11, 11-18, 18-45, 45-60, and >60 yrs. Results: A total of 1885 were included in the study after exclusion (775 males and 1110 females). The case rate was highest for 18- 45yrs age group. Among communicable diseases Upper respira- tory tract infections (URTI) (67.06%) and acute gastroenteritis (12.55%) had maximum burden. Musculoskeletal pains (26.55%) and hypertension (15.53%) were the most reported diseases among non-communicable diseases. Females outnumbered males in most of the diseases. Most of the diseases were observed more in winters. Conclusion: The relatively higher burden of non-communicable diseases hints towards entering of the transition phase in India, an eye opener for the health planners to equip themselves against these diseases and develop appropriate health care policies and practices. Many diseases have seasonal variation and the burden of these diseases can be reduced by steps taken by the health planners and manager beforehand and through implementation of surveillance programs.